Efficiency of EU merger control in the 1990-2008 period - Goran Serdarević; Petr Teplý (Charles University in Prague, Institute of Economic Studies (IES), 2009)
The main goal of this paper is to provide an analysis of key regulatory changes in the European merger control and to evaluate their real impact on the efficiency of merger regulation. Our main contribution is an empirical analysis of a unique representative sample of 161 horizontal mergers covering the final regulatory assessments during the period from 1990 to 2008. We use stock market data to identify those cases where there are discrepancies between the Commission and market evaluation of the merger. The PROBIT model is then used to further investigate the sources of these discrepancies. Our results suggest that the Commission's decisions are not purely explained by the motive of protecting consumer welfare and that other political and institutional factors do play a role in setting policy. We did not find evidence that the Commission protects competitors at the expense of consumers and foreign firms. Moreover, we conclude that the regulatory reform introduced in 2004 has significantly enhanced efficiency of the European merger control. To the authors' best knowledge, this paper is the first study using stock market data to evaluate an impact of the recent EU merger control.
Keywords: L4; K21; C25; D78; 330; merger control; European Union; political economy; regulatory reform; PROBIT model; Fusionskontrolle; Regulierung; EU-Politik; EU-Staaten